The relationship between mobile phone addiction, bedtime procrastination, and campus-based physical activity: a longitudinal follow-up study based on a college student population - Deng, Mingcai; Li, Zhi (Frontiers in Psychology, 2025)
ObjectiveTo examine the relationship between mobile phone addiction (MPA), bedtime procrastination (BP), and campus-based physical activity (CBPA) among university students, and to determine whether a “vicious circle” mechanism contributes to health risks, thereby providing a foundation for developing good habits and promoting the overall physical and mental health of university students.DesignUsing the cross-lagged panel model (CLPM) and AMOS 26.0, the analysis was carried out in three steps: “controlling for stability effects - analyzing cross-time predictive paths—testing model fit” to explore the cross-time predictive pathways and mechanisms of action among MPA, BP, and CBPA, and to examine the longitudinal interaction relationships among these variables.MethodsTwo longitudinal follow-up surveys of 376 university students at 3-month intervals using the Mobile Phone Addiction Scale, the Bedtime Procrastination Scale, and the Physical Activity Rating Scale (2025/03/10-2025/06/13).Results(1) T1 MPA was significantly and positively correlated with T1 BP (r = 0.277, p < 0.01) and significantly and negatively correlated with T1 CBPA (r = –0.319, p < 0.01); T2 MPA was significantly and positively correlated with T2 BP (r = 0.433, p < 0.01) and significantly and negatively correlated with T2 CBPA (r = –0.339, p < 0.01). (2) The effect of T1 MPA on both T2 BP (β = 0.27) and T2 CBPA (β = –0.17) was significant (p < 0.01). T1 BP on T2 MPA was significant (β = 0.27, p < 0.01), and T1 CBPA on T2 BP was significant (β = –0.17, p < 0.01).Conclusion(1) There is preliminary longitudinal evidence that MPA and BP can mutually provide for each other and form a “vicious cycle” mechanism. (2) There is preliminary longitudinal evidence that MPA provides for CBPA. (3) There is preliminary longitudinal evidence that CBPA provides for BP.